Method for producing coating film-forming composition for lithography

JP7652210B2Active Publication Date: 2025-03-27NISSAN CHEM CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023063316
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-12-20
Filing Date
2023-04-10
Publication Date
2025-03-27
Estimated Expiration
2039-12-18

Smart Images

  • Figure 0007652210000001
    Figure 0007652210000001
  • Figure 0007652210000002
    Figure 0007652210000002
  • Figure 0007652210000003
    Figure 0007652210000003
Patent Text Reader

Abstract

To reduce metal impurities which cause minute defects on a wafer.SOLUTION: A method for producing a coating film-forming composition for lithography includes a step of passing a liquid through a filter cartridge, wherein the filter cartridge is one having a plurality of kinds of base fabrics for filtration laminated or wound around a hollow inner cylinder, the base fabrics for filtration are non-woven fabrics obtained by chemically bonding a metal adsorption group to a polyolefin fiber, the base fabrics for filtration comprise a non-woven fabric layer A and a non-woven fabric layer B, the non-woven fabric layer A is composed of a polyolefin fiber obtained by chemically bonding a sulfonic acid group as the metal adsorption group, and the non-woven fabric layer B is composed of a polyolefin fiber obtained by chemically bonding at least one selected from an amino group, an N-methyl-D-glucamine group, an iminodiacetic acid group, an iminodiethanol group, an amidoxime group, a phosphoric acid group, a carboxylic acid group and an ethylenediaminetriacetic acid group as the metal adsorption group.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a method for producing a composition for forming a coating film for lithography, in which metal impurities that cause defects in the lithography process used in the manufacture of semiconductor devices are reduced. [Background technology]

[0002] For lithography coating film-forming compositions used in the lithography process in the manufacture of semiconductor devices, there is a demand for reduction of metal impurities that cause minute defects (for example, about 1 to 100 nm, called defects) on wafers. Patent Document 1 discloses a filter that has high efficiency in adsorbing and removing metals. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 2018-167223 Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to provide a method for producing a composition for forming a coating film for lithography, in which metal impurities that cause microdefects on wafers are reduced in the lithography process in the manufacture of semiconductor devices, and a method for reducing metals in a precursor of a composition for forming a coating film for lithography. [Means for solving the problem]

[0005] The present invention encompasses the following. [1] A method for producing a coating film-forming composition for lithography, comprising a step of passing a coating film-forming composition for lithography through a metal-removing filter cartridge, wherein the metal-removing filter cartridge is A filter cartridge in which multiple types of filtration fabrics are laminated or wound around a hollow inner cylinder, The filtering base fabric is a nonwoven fabric in which metal adsorption groups are chemically bonded to polyolefin fibers, The filtering base fabric includes a nonwoven fabric layer A and a nonwoven fabric layer B, The nonwoven fabric layer A is composed of polyolefin fibers to which sulfonic acid groups are chemically bonded as metal adsorption groups, The method for producing a coating film-forming composition for lithography, wherein the nonwoven fabric layer B is a filter cartridge characterized by being composed of polyolefin fibers having at least one metal-adsorbing group chemically bonded thereto selected from the group consisting of an amino group, an N-methyl-D-glucamine group, an iminodiacetic acid group, an iminodiethanol group, an amidoxime group, a phosphate group, a carboxylic acid group, and an ethylenediaminetriacetic acid group. [2] The method for producing a composition for forming a coating film for lithography according to [1], further comprising a step of passing the composition through a filter cartridge for removing fine particles. [3] The method for producing a composition for forming a coating film for lithography according to [2], wherein the material of the filter for removing fine particles is at least one selected from the group consisting of polyethylene and nylon. [4] The method for producing a resist underlayer film-forming composition according to any one of [1] to [3], wherein the coating film-forming composition for lithography is a resist underlayer film-forming composition. [5] The method for producing a resist underlayer film-forming composition according to [4], wherein the composition for forming a coating film for lithography contains a polymer having a weight average molecular weight of 800 or more and an organic solvent. [6] The method for producing a resist underlayer film-forming composition according to [4] or [5], wherein the resist underlayer film-forming composition further contains a crosslinkable compound. [7] The method for producing a resist underlayer film-forming composition according to any one of [4] to [6], wherein the resist underlayer film-forming composition further contains a crosslinking catalyst. [8] The method for producing a resist underlayer film-forming composition according to any one of [4] to [7], wherein the resist underlayer film-forming composition further contains a surfactant. [9] A method for reducing metals by passing a precursor of a coating film-forming composition for lithography through a cartridge filter for removing metals, comprising: The filter cartridge is made by laminating or winding a plurality of types of filtration fabrics around a hollow inner cylinder, The filtering base fabric is a nonwoven fabric in which metal adsorption groups are chemically bonded to polyolefin fibers, The filtering base fabric includes a nonwoven fabric layer A and a nonwoven fabric layer B, The nonwoven fabric layer A is composed of polyolefin fibers to which sulfonic acid groups are chemically bonded as metal adsorption groups, The method for reducing metals in a coating film-forming composition precursor for lithography, wherein the nonwoven fabric layer B is a filter cartridge composed of polyolefin fibers having at least one metal adsorption group chemically bonded thereto selected from the group consisting of an amino group, an N-methyl-D-glucamine group, an iminodiacetic acid group, an iminodiethanol group, an amidoxime group, a phosphate group, a carboxylic acid group, and an ethylenediaminetriacetic acid group.

[10] [4] - [8]. A method for producing a substrate having a resist pattern, the method comprising the steps of: applying the resist underlayer film-forming composition according to any one of [4] to [8] onto a semiconductor substrate and baking the composition to form a resist underlayer film; forming a resist film on the resist underlayer film; and then exposing and developing the resist film to form a resist pattern, the method being used in the production of a semiconductor.

[11] A method for manufacturing a semiconductor device, comprising the steps of forming a resist underlayer film on a semiconductor substrate, on the surface of which an inorganic film may be formed, using the resist underlayer film-forming composition according to any one of [4] to [8], forming a resist pattern on the resist underlayer film, dry-etching the resist underlayer film using the resist pattern as a mask to expose a surface of the inorganic film or the semiconductor substrate, and processing the inorganic film or the semiconductor substrate by dry-etching using the resist and resist underlayer film after dry etching as masks.

[12] A method for producing an organic solvent for a composition for forming a coating film for lithography, comprising a step of passing a liquid through a metal-removing filter cartridge, wherein the metal-removing filter cartridge is A filter cartridge in which multiple types of filtration fabrics are laminated or wound around a hollow inner cylinder, The filtering base fabric is a nonwoven fabric in which metal adsorption groups are chemically bonded to polyolefin fibers, The filtering base fabric includes a nonwoven fabric layer A and a nonwoven fabric layer B, The nonwoven fabric layer A is composed of polyolefin fibers to which sulfonic acid groups are chemically bonded as metal adsorption groups, The method for producing an organic solvent for a composition for forming a coating film for lithography is a filter cartridge characterized in that the nonwoven fabric layer B is made of polyolefin fibers having at least one metal-adsorbing group chemically bonded thereto selected from the group consisting of an amino group, an N-methyl-D-glucamine group, an iminodiacetic acid group, an iminodiethanol group, an amidoxime group, a phosphate group, a carboxylic acid group, and an ethylenediaminetriacetic acid group.

[13] A method for producing a solvent for a composition for forming a coating film for lithography, comprising a step of passing a solvent through a metal-removing filter cartridge, wherein the metal-removing filter cartridge is A filter cartridge in which multiple types of filtration fabrics are laminated or wound around a hollow inner cylinder, The filtering base fabric is a nonwoven fabric in which metal adsorption groups are chemically bonded to polyolefin fibers, The filtering base fabric includes a nonwoven fabric layer A and a nonwoven fabric layer B, The nonwoven fabric layer A is composed of polyolefin fibers to which sulfonic acid groups are chemically bonded as metal adsorption groups, The method for producing a solvent for a composition for forming a coating film for lithography, wherein the nonwoven fabric layer B is a filter cartridge characterized by being composed of polyolefin fibers having at least one metal adsorption group chemically bonded thereto selected from the group consisting of an amino group, an N-methyl-D-glucamine group, an iminodiacetic acid group, an iminodiethanol group, an amidoxime group, a phosphate group, a carboxylic acid group, and an ethylenediaminetriacetic acid group. [Effects of the Invention]

[0006] By using the filter cartridge of the present invention to produce a composition for forming a coating film for lithography, it is possible to produce a composition for forming a coating film for lithography with significantly reduced metal impurities, and various micro-defects that occur in the lithography process in semiconductor manufacturing processes can be reduced. DETAILED DESCRIPTION OF THE INVENTION

[0007] <Method for producing coating film-forming composition for lithography> The method for producing a coating film-forming composition for lithography of the present invention includes the steps of producing a coating film-forming composition precursor for lithography that is in a solution state at room temperature, and then passing the composition precursor through a metal-removing filter cartridge, which will be described in detail below.

[0008] The liquid passing step is carried out, for example, by producing a lithography coating film-forming composition precursor by a method known per se and then passing the liquid through a metal-removing filter cartridge directly connected (at two points, an inlet and an outlet) to the composition production equipment (production vessel). The liquid passing step may be carried out once or twice or more times, but is preferably circulating filtration using a pump. It is preferable to circulate the liquid by passing it through both the metal-removing filter cartridge of the present application and a particulate-removing filter cartridge connected in series upstream or downstream of the metal-removing filter cartridge. The time required for circulation is, for example, 3 to 144 hours, 6 to 72 hours, or 12 to 48 hours. The filtration flow rate is, for example, 1 to 1,000 L / hour, 10 to 500 L / hour, or 20 to 100 L / hour.

[0009] <Precursor for coating film-forming composition for lithography> The coating film-forming composition precursor for lithography used in the present application is, for example, a photoresist composition described below, a resist underlayer film-forming composition (containing an organic compound and / or an inorganic compound), a protective film-forming composition for protecting a substrate from an etching solution during semiconductor substrate processing, an underlayer film-forming composition for a self-assembled film, an overlayer film-forming composition for a self-assembled film, and a resist overlayer film-forming composition, etc., which are compositions before passing through the filter cartridge as specified above, but are not limited to these.

[0010] The exposure wavelength in the lithography process may be i-line, KrF excimer laser, ArF excimer laser, EUV (extreme ultraviolet) or EB (electron beam). Other examples of the composition include resist upper layer film-forming compositions for resist upper layer films described in WO2014 / 115843, WO2015 / 129486, etc.; underlayer film-forming compositions for self-assembled films utilizing block copolymer self-assembly (Direct Self Assembly, DSA) technology described in WO2013 / 146600, WO2014 / 097993, etc., such as an overlayer film-forming composition for the self-assembled film described in WO2018 / 051907; and a coating composition for pattern reversal described in WO2016 / 031563.

[0011] Examples of the precursor include photoresist compositions (positive and negative) for photoresist films known per se, which are formed by applying the precursor to a semiconductor wafer, preferably by spin coating, followed by a baking process; resist underlayer film-forming compositions (containing an organic compound and / or an inorganic compound) for resist underlayer films known per se; protective film-forming compositions for semiconductor substrate protective films used when wet etching a semiconductor substrate known per se; resist toplayer film-forming compositions for resist toplayer films known per se; underlayer film-forming compositions for self-assembled films known per se; and toplayer film-forming compositions for self-assembled films known per se, with preferred being protective film-forming compositions or resist underlayer film-forming compositions. Preferred are resist underlayer film-forming compositions. Preferred are resist underlayer film-forming compositions for ArF, EUV, or EB. Preferred are underlayer film-forming compositions for self-assembled films. Preferred are toplayer film-forming compositions for self-assembled films. Preferred are resist toplayer film-forming compositions for EUV. Preferred are coating compositions for pattern reversal.

[0012] Examples of the resist underlayer film-forming composition include those described in WO2009 / 096340, JP2009-053704A, WO2010 / 147155A, WO2011 / 102470A, WO2013 / 047516A, WO2015 / 030060A, WO2018 / 052130A, WO2019 / 1 Examples of the protective film-forming composition, the resist underlayer-forming composition, and the silicon-containing resist underlayer film-forming composition are those described in Patent Publication Nos. 2019-24474, 2019-124475, 2019-151471, PCT / JP2019 / 042708, Japanese Patent Application Nos. 2019-007857, 2019-088345, etc.

[0013] The solids content of the coating film-forming composition for lithography and the coating film-forming composition precursor for lithography according to the present invention is typically 0.1 to 70% by mass, preferably 0.1 to 60% by mass, and more preferably 0.1 to 40% by mass. The solids content refers to the content of all components in the coating film-forming composition for lithography excluding the solvent. The proportion of the polymer in the solids content is, for example, 1 to 100% by mass, 2 to 100% by mass, 3 to 100% by mass, 4 to 100% by mass, 5 to 100% by mass, 10 to 100% by mass, 30 to 100% by mass, 50 to 100% by mass, 6 to 100% by mass, 1 to 99.9% by mass, 50 to 99.9% by mass, 50 to 95% by mass, or 50 to 90% by mass.

[0014] <Polymer> The coating film-forming composition for lithography used in the present application preferably contains a polymer having a weight average molecular weight of 800 or more and an organic solvent. An example of a specific structure of the polymer is the following formula (1):

[0015] [ka]

[0016] [In the above formula, X represents the following formula (2), formula (3), or formula (4): [ka]

[0017] (In the above formula, R 1 ~R 5 each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, a benzyl group, or a phenyl group, and the phenyl group may be substituted with at least one group selected from the group consisting of an alkyl group having 1 to 6 carbon atoms, a halogen atom, an alkoxy group having 1 to 6 carbon atoms, a nitro group, a cyano group, and an alkylthio group having 1 to 6 carbon atoms; and R 1 and R 2 , R 3 and R 4may be bonded to each other to form a ring having 3 to 6 carbon atoms; A 1 ~A 6 each independently represents a hydrogen atom, a methyl group, or an ethyl group; Q 1 represents a divalent group containing a disulfide bond, preferably a divalent group containing an alkylene group having 1 to 6 carbon atoms at each end of the disulfide bond, n is the number of repeating structural units and represents an integer of 5 to 100. It is preferable that the unit structure be represented by the following formula: Examples of the polymer of the present application include, but are not limited to, the polymers described in International Publication No. 2009 / 096340 and reaction products of bifunctional or higher functional compounds having at least one disulfide bond and trifunctional or higher functional compounds described in Japanese Patent Application No. 2018-121282. When the polymer is a reaction product of a bifunctional compound (A) having at least one disulfide bond and a bifunctional compound (B) different from the compound (A), the disulfide bond is present in the main chain of the polymer. The polymer has the following formula (1): [ka] (In the above formula (1), R1 is an alkyl group having 0 to 1 carbon atoms, n is the number of repeating unit structures and represents an integer of 0 or 1, and m is an integer of 0 or 1.) In the above formula (1), Z1 is the following formula (2) or formula (3): [ka] In the above formula (3), X is the following formula (4), formula (51), or formula (6): [ka] In the above formula (1), R2~R 61 (R2, R3, R4, R 51 and R61 each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 3 to 6 carbon atoms, a benzyl group, or a phenyl group, and the phenyl group may be substituted with at least one group selected from the group consisting of an alkyl group having 1 to 6 carbon atoms, a halogen atom, an alkoxy group having 1 to 6 carbon atoms, a nitro group, a cyano group, and an alkylthio group having 1 to 6 carbon atoms, and R2 and R3, and R4 and R5 may be bonded to each other to form a ring having 3 to 6 carbon atoms. A1 to A6 each independently represent a hydrogen atom, a methyl group, or an ethyl group; Q1 represents an alkylene group having 1 to 10 carbon atoms interrupted by a disulfide bond; l is the number of repeating unit structures and represents an integer of 5 to 100. The compound may have a repeating unit structure represented by the following formula: Q1 is preferably an alkylene group of 2 to 6 carbon atoms interrupted by a disulfide bond. Examples of the "ring having 3 to 6 carbon atoms" include cyclopropane, cyclobutane, cyclopentane, cyclopentadiene, and cyclohexane. The above formula (1) can be expressed by the following formula (5): [ka] [In the above formula (5), X represents a group represented by the above formula (4), formula (51), or formula (6), and R 6 and R 7 each independently represents an alkylene group having 1 to 3 carbon atoms or a direct bond, p is the number of repeating unit structures and represents an integer of 5 to 100. It may be expressed as: The polymer of the present invention is preferably represented by the following formulas P-6 to P-8. [ka] [ka] [ka] The polymer is preferably a reaction product synthesized by reacting a bifunctional or higher functional compound (A) having at least one disulfide bond with a bifunctional or higher functional compound (B) by a method known per se.

[0018] Examples of the alkyl group having 1 to 6 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an i-propyl group, a cyclopropyl group, an n-butyl group, an i-butyl group, an s-butyl group, a t-butyl group, a cyclobutyl group, a 1-methyl-cyclopropyl group, a 2-methyl-cyclopropyl group, an n-pentyl group, a 1-methyl-n-butyl group, a 2-methyl-n-butyl group, a 3-methyl-n-butyl group, a 1,1-dimethyl-n-propyl group, a 1,2-dimethyl-n-propyl group, a 2,2-dimethyl-n-propyl group, and a 1-ethyl-n-propyl group. , cyclopentyl group, 1-methyl-cyclobutyl group, 2-methyl-cyclobutyl group, 3-methyl-cyclobutyl group, 1,2-dimethyl-cyclopropyl group, 2,3-dimethyl-cyclopropyl group, 1-ethyl-cyclopropyl group, 2-ethyl-cyclopropyl group, n-hexyl group, 1-methyl-n-pentyl group, 2-methyl-n-pentyl group, 3-methyl-n-pentyl group, 4-methyl-n-pentyl group, 1,1-dimethyl-n-butyl group, 1,2-dimethyl-n-butyl group, 1,3-dimethyl-n-butyl group, 2,2 -dimethyl-n-butyl group, 2,3-dimethyl-n-butyl group, 3,3-dimethyl-n-butyl group, 1-ethyl-n-butyl group, 2-ethyl-n-butyl group, 1,1,2-trimethyl-n-propyl group, 1,2,2-trimethyl-n-propyl group, 1-ethyl-1-methyl-n-propyl group, 1-ethyl-2-methyl-n-propyl group, cyclohexyl group, 1-methyl-cyclopentyl group, 2-methyl-cyclopentyl group, 3-methyl-cyclopentyl group, 1-ethyl-cyclobutyl group, 2-ethyl-cyclobutyl group, 3-ethyl-cyclobutyl, 1,2-dimethyl-cyclobutyl, 1,3-dimethyl-cyclobutyl, 2,2-dimethyl-cyclobutyl, 2,3-dimethyl-cyclobutyl, 2,4-dimethyl-cyclobutyl, 3,3-dimethyl-cyclobutyl, 1-n-propyl-cyclopropyl, 2-n-propyl-cyclopropyl, 1-i-propyl-cyclopropyl, 2-i-propyl-cyclopropyl, 1,2,2-trimethyl-cyclopropyl, 1,2,3-trimethyl-cyclopropyl, 2,2,Examples include a 3-trimethyl-cyclopropyl group, a 1-ethyl-2-methyl-cyclopropyl group, a 2-ethyl-1-methyl-cyclopropyl group, a 2-ethyl-2-methyl-cyclopropyl group, and a 2-ethyl-3-methyl-cyclopropyl group.

[0019] Examples of the alkenyl group having 2 to 6 carbon atoms include a vinyl group, an allyl group, a propenyl group, a butenyl group, a hexenyl group, and a cyclohexenyl group.

[0020] Examples of the alkoxy group having 1 to 6 carbon atoms include a methoxy group, an ethoxy group, an n-propoxy group, an isopropoxy group, an n-butoxy group, a t-butoxy group, a cyclopentyloxy group, and a cyclohexyloxy group.

[0021] Examples of the alkylthio group having 1 to 10 carbon atoms include an ethylthio group, a butylthio group, a hexylthio group, and an octylthio group.

[0022] The alkylene group having 1 to 6 carbon atoms is a divalent organic group corresponding to the alkyl group, such as a methylene group, an ethylene group, an n-propylene group, an isopropylene group, a cyclopropylene group, an n-butylene group, an isobutylene group, an s-butylene group, a t-butylene group, a cyclobutylene group, a 1-methyl-cyclopropylene group, a 2-methyl-cyclopropylene group, an n-pentylene group, a 1-methyl-n-butylene group, a 2-methyl-n-butylene group, a 3-methyl-n-butylene group, a 1,1-dimethyl-n-propylene group, a 1,2-dimethyl-n-propylene group, a 2,2 -dimethyl-n-propylene, 1-ethyl-n-propylene, cyclopentylene, 1-methyl-cyclobutylene, 2-methyl-cyclobutylene, 3-methyl-cyclobutylene, 1,2-dimethyl-cyclopropylene, 2,3-dimethyl-cyclopropylene, 1-ethyl-cyclopropylene, 2-ethyl-cyclopropylene, n-hexylene, 1-methyl-n-pentylene, 2-methyl-n-pentylene, 3-methyl-n-pentylene, 4-methyl-n-pentylene, 1,1-dimethyl-n-butylene, 1,2-dimethyl-n -butylene group, 1,3-dimethyl-n-butylene group, 2,2-dimethyl-n-butylene group, 2,3-dimethyl-n-butylene group, 3,3-dimethyl-n-butylene group, 1-ethyl-n-butylene group, 2-ethyl-n-butylene group, 1,1,2-trimethyl-n-propylene group, 1,2,2-trimethyl-n-propylene group, 1-ethyl-1-methyl-n-propylene group, 1-ethyl-2-methyl-n-propylene group, cyclohexylene group, 1-methyl-cyclopentylene group, 2-methyl-cyclopentylene group, 3-methyl-cyclopentylene group, 1-ethyl -cyclobutylene group, 2-ethyl-cyclobutylene group, 3-ethyl-cyclobutylene group, 1,2-dimethyl-cyclobutylene group, 1,3-dimethyl-cyclobutylene group, 2,2-dimethyl-cyclobutylene group, 2,3-dimethyl-cyclobutylene group, 2,4-dimethyl-cyclobutylene group, 3,3-dimethyl-cyclobutylene group, 1-n-propyl-cyclopropylene group, 2-n-propyl-cyclopropylene group, 1-isopropyl-cyclopropylene group, 2-isopropyl-cyclopropylene group, 1,2,2-trimethyl-cyclopropylene group, 1,2,Examples include a 3-trimethyl-cyclopropylene group, a 2,2,3-trimethyl-cyclopropylene group, a 1-ethyl-2-methyl-cyclopropylene group, a 2-ethyl-1-methyl-cyclopropylene group, a 2-ethyl-2-methyl-cyclopropylene group, and a 2-ethyl-3-methyl-cyclopropylene group.

[0023] Polymers having a weight average molecular weight of 800 or more, for example, 800 to 100,000, 1,500 to 50,000, 2,000 to 30,000, or 3,000 to 20,000, can be used. The weight average molecular weight can be determined, for example, under the following conditions. Apparatus: Tosoh Corporation HLC-8320GPC GPC column: Shodex (registered trademark) Asahipak (registered trademark) (Showa Denko K.K.) Column temperature: 40℃ Flow rate: 0.35mL / min Eluent: tetrahydrofuran (THF) Standard sample: Polystyrene (Tosoh Corporation)

[0024] <Organic solvents> The coating film-forming composition for lithography of the present invention can be prepared by dissolving the above-mentioned components in an organic solvent, and is used in the state of a homogeneous solution.

[0025] The organic solvent for the coating film-forming composition for lithography according to the present invention can be any solvent that can dissolve the above-mentioned components. In particular, since the coating film-forming composition for lithography and the coating film-forming composition precursor for lithography according to the present invention are used in the form of a homogeneous solution, it is recommended to use an organic solvent that is commonly used in lithography processes, taking into account their coating performance.

[0026] Examples of the organic solvent include ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, methyl cellosolve acetate, ethyl cellosolve acetate, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, propylene glycol, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monomethyl ether acetate, propylene glycol propyl ether acetate, toluene, xylene, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, and cyclohexanone. Examples of the solvent include cyclopentane, cycloheptanone, 4-methyl-2-pentanol, methyl 2-hydroxyisobutyrate, ethyl 2-hydroxyisobutyrate, ethyl ethoxyacetate, 2-hydroxyethyl acetate, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, ethyl 3-ethoxypropionate, methyl 3-ethoxypropionate, methyl pyruvate, ethyl pyruvate, ethyl acetate, butyl acetate, ethyl lactate, butyl lactate, 2-heptanone, methoxycyclopentane, anisole, γ-butyrolactone, N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide. These solvents can be used alone or in combination of two or more.

[0027] Among these solvents, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, ethyl lactate, butyl lactate, cyclohexanone, etc. are preferred, with propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate being particularly preferred.

[0028] <Crosslinkable compound> The coating film-forming composition for lithography used in the present application preferably contains a crosslinking compound. Examples of crosslinking compounds include melamine-based compounds, substituted urea-based compounds, and polymers thereof, as well as epoxy-based compounds and polymers thereof, and blocked isocyanate-based compounds and polymers thereof. A crosslinking compound having at least two crosslink-forming substituents is preferred, such as methoxymethylated glycoluril, butoxymethylated glycoluril, methoxymethylated melamine, butoxymethylated melamine, methoxymethylated benzoguwanamine, butoxymethylated benzoguwanamine, methoxymethylated urea, butoxymethylated urea, methoxymethylated thiourea, or methoxymethylated thiourea. A specific example is tetramethoxymethylglycoluril. Condensates of these compounds can also be used.

[0029] Furthermore, a crosslinking agent with high heat resistance can be used as the crosslinkable compound, such as a compound containing a crosslink-forming substituent with an aromatic ring (e.g., a benzene ring or a naphthalene ring) in the molecule. This compound may be a compound having a partial structure of the following formula (5-1), or a polymer or oligomer having a repeating unit of the following formula (5-2).

[0030] [ka]

[0031] Above R 11 , R 12 , R 13 , and R 14 is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and the alkyl groups mentioned above can be used.

[0032] m1 is 1≦m1≦6−m2, m2 is 1≦m2≦5, m3 is 1≦m3≦4−m2, and m4 is 1≦m4≦3.

[0033] Examples of the compounds, polymers and oligomers of formula (5-1) and formula (5-2) are shown below.

[0034] [ka]

[0035] [ka]

[0036] The above compounds are available as products of Asahi Organic Chemicals Co., Ltd. and Honshu Chemical Industry Co., Ltd. For example, among the above crosslinking agents, the compound of formula (6-22) is available from Asahi Organic Chemicals Co., Ltd. under the trade name TMOM-BP. The crosslinking agent may also be a compound having at least two epoxy groups. Examples of such compounds include tris(2,3-epoxypropyl)isocyanurate, 1,4-butanediol diglycidyl ether, 1,2-epoxy-4-(epoxyethyl)cyclohexane, glycerol triglycidyl ether, diethylene glycol diglycidyl ether, 2,6-diglycidylphenyl glycidyl ether, 1,1,3-tris[p-(2,3-epoxypropoxy)phenyl]propane, 1,2-cyclohexanedicarboxylic acid diglycidyl ester, 4,4'-methylenebis(N,N-diglycidylaniline), 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, trimethylolethane triglycidyl ether, bisphenol-A diglycidyl ether, and Epolead (registered trademark) GT-401, GT-403, GT-301, and GT-30 manufactured by Daicel Corporation. 2. Celloxide (registered trademark) 2021, 3000, 1001, 1002, 1003, 1004, 1007, 1009, 1010, 828, 807, 152, 154, 180S75, 871, 872 manufactured by Mitsubishi Chemical Corporation, EPPN201, 202, EOCN-102, 103S, 104S, 1020, 1025, 1027 manufactured by Nippon Kayaku Co., Ltd., and Denacol (registered trademark) EX-25 manufactured by Nagase ChemteX Corporation. 2, EX-611, EX-612, EX-614, EX-622, EX-411, EX-512, EX-522, EX-421, EX-313, EX-314, EX-321, CY175, CY177, CY179, CY182, CY184, CY192 manufactured by BASF Japan Ltd., and Epiclon 200, 400, 7015, 835LV, and 850CRP manufactured by DIC Corporation.

[0037] The compound having at least two epoxy groups can also be a polymer having an epoxy group. Any polymer having an epoxy group can be used without particular limitations. Such polymers can be produced by addition polymerization using an addition-polymerizable monomer having an epoxy group, or by reacting a polymer compound having a hydroxy group with a compound having an epoxy group, such as epichlorohydrin or glycidyl tosylate. Examples of such polymers include addition-polymerized polymers such as polyglycidyl acrylate, copolymers of glycidyl methacrylate and ethyl methacrylate, copolymers of glycidyl methacrylate, styrene, and 2-hydroxyethyl methacrylate, and condensation-polymerized polymers such as epoxy novolac. The weight-average molecular weight of the polymer is, for example, 300 to 200,000. The weight-average molecular weight is a value obtained by gel permeation chromatography (GPC) using polystyrene as a standard sample.

[0038] The compound having at least two epoxy groups may also be an epoxy resin having an amino group, such as YH-434 or YH-434L (manufactured by Shin-Nichika Epoxy Manufacturing Co., Ltd. (formerly Tohto Kasei Co., Ltd.)).

[0039] The crosslinking agent may also be a compound having at least two blocked isocyanate groups. Examples of such compounds include Takenate (registered trademark) B-830 and B-870N manufactured by Mitsui Chemicals, Inc., and VESTANAT (registered trademark) B1358 / 100 manufactured by Evonik Degussa. These crosslinking agents may be used alone or in combination of two or more.

[0040] The amount of crosslinking compound added varies depending on the coating solvent used, the base substrate used, the required solution viscosity, the required film shape, etc., but is usually 0.001 to 80 wt %, preferably 0.01 to 50 wt %, and more preferably 0.1 to 40 wt %, based on the total solids content of the coating film-forming composition for lithography and the coating film-forming composition precursor for lithography. These crosslinking compounds may undergo a crosslinking reaction by self-condensation, but when crosslinkable substituents are present in the above-mentioned polymer of the present invention, they can undergo a crosslinking reaction with those crosslinkable substituents.

[0041] <Crosslinking catalyst> The coating film-forming composition for lithography and the coating film-forming composition precursor for lithography of the present invention may contain a crosslinking catalyst as an optional component to promote the crosslinking reaction. As the crosslinking catalyst, in addition to an acidic compound (crosslinking acid catalyst), a compound that generates an acid or a base upon heating can be used. As the acidic compound, a sulfonic acid compound or a carboxylic acid compound can be used, and as a compound that generates an acid upon heating, a thermal acid generator can be used. Among these, it is preferable to use a crosslinking acid catalyst.

[0042] Examples of sulfonic acid compounds or carboxylic acid compounds include ammonium trifluoroacetic acid, p-toluenesulfonic acid, trifluoromethanesulfonic acid, pyridinium trifluoromethanesulfonate, pyridinium-p-toluenesulfonate, pyridinium-4-hydroxybenzenesulfonate, salicylic acid, camphorsulfonic acid, 5-sulfosalicylic acid, 4-chlorobenzenesulfonic acid, 4-hydroxybenzenesulfonic acid, pyridinium-4-hydroxybenzenesulfonic acid, benzenedisulfonic acid, 1-naphthalenesulfonic acid, 4-nitrobenzenesulfonic acid, citric acid, benzoic acid, and hydroxybenzoic acid.

[0043] Examples of thermal acid generators include K-PURE (registered trademark) CXC-1612, CXC-1614, TAG-2172, TAG-2179, TAG-2678, and TAG2689 (all manufactured by King Industries), and SI-45, SI-60, SI-80, SI-100, SI-110, and SI-150 (all manufactured by Sanshin Chemical Industry Co., Ltd.).

[0044] These crosslinking catalysts can be used alone or in combination of two or more. When the coating film-forming composition for lithography contains a crosslinking catalyst, the content thereof is usually 0.0001 to 20% by weight, preferably 0.01 to 15% by weight, and more preferably 0.1 to 10% by mass, based on the total solid content of the coating film-forming composition for lithography.

[0045] <Surfactant> The coating film-forming composition for lithography used in the present invention may contain a surfactant as an optional component to improve its coatability on semiconductor substrates. Examples of such surfactants include polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene cetyl ether, and polyoxyethylene oleyl ether; polyoxyethylene alkylaryl ethers such as polyoxyethylene octylphenyl ether and polyoxyethylene nonylphenyl ether; polyoxyethylene-polyoxypropylene block copolymers; sorbitan fatty acid esters such as sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan monooleate, sorbitan trioleate, and sorbitan tristearate; polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, and polyoxyethylene sorbitan monostearate; nonionic surfactants such as polyoxyethylene sorbitan fatty acid esters, such as polyoxyethylene sorbitan trioleate and polyoxyethylene sorbitan tristearate; fluorine-containing surfactants such as F-TOP (registered trademark) EF301, EF303, and EF352 (manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.), Megafac (registered trademark) F171, F173, R-30, R-30N, R-40, and R-40-LM (manufactured by DIC Corporation), Fluorad FC430 and FC431 (manufactured by Sumitomo 3M Limited), Asahiguard (registered trademark) AG710, Surflon (registered trademark) S-382, SC101, SC102, SC103, SC104, SC105, and SC106 (manufactured by Asahi Glass Co., Ltd.); and organosiloxane polymer KP341 (manufactured by Shin-Etsu Chemical Co., Ltd.). These surfactants can be used alone or in combination of two or more. When the coating film-forming composition for lithography contains a surfactant, the content thereof is usually 0.0001 to 10 wt %, preferably 0.01 to 5 wt %, based on the total solid content of the coating film-forming composition for lithography.

[0046] <Other ingredients> The coating film-forming composition for lithography of the present invention may contain a light absorber, a rheology modifier, an adhesion promoter, etc. The rheology modifier is effective in improving the fluidity of the coating film-forming composition for lithography. The adhesion promoter is effective in improving the adhesion between the semiconductor substrate or resist and the underlayer film.

[0047] <Filter cartridge> The filter cartridge used in the present invention is preferably the one described in JP 2018-167223 A.

[0048] The filter cartridge used in the present invention is a filter cartridge in which multiple types of filtration base fabrics are laminated or wound around a hollow inner cylinder, and the filtration base fabric is a nonwoven fabric in which metal adsorption groups are chemically bonded to polyolefin fibers. The filtration base fabric includes nonwoven fabric layer A and nonwoven fabric layer B, and nonwoven fabric layer A is composed of polyolefin fibers to which sulfonic acid groups are chemically bonded as metal adsorption groups, and nonwoven fabric layer B is composed of polyolefin fibers to which at least one metal adsorption group selected from the group consisting of amino groups, N-methyl-D-glucamine groups, iminodiacetic acid groups, iminodiethanol groups, amidoxime groups, phosphate groups, carboxylic acid groups, and ethylenediaminetriacetic acid groups is chemically bonded as a metal adsorption group.

[0049] The filter cartridge used in the present invention is a filter cartridge in which multiple types of filtration fabrics are laminated or wrapped around a hollow inner cylinder. The filtration fabric is a nonwoven fabric in which metal-adsorbing groups are chemically bonded to polyolefin fibers. The filtration fabric includes nonwoven fabric layer A and nonwoven fabric layer B. Nonwoven fabric layer A is composed of polyolefin fibers to which sulfonic groups are chemically bonded as metal-adsorbing groups, and nonwoven fabric layer B is composed of polyolefin fibers to which at least one metal-adsorbing group selected from the group consisting of amino groups, N-methyl-D-glucamine groups, iminodiacetic acid groups, iminodiethanol groups, amidoxime groups, phosphate groups, carboxylic acid groups, and ethylenediaminetriacetic acid groups is chemically bonded as a metal-adsorbing group. This allows for efficient metal removal. Note that multiple types of filtration fabrics also include a single filtration fabric formed by bonding different types of filtration fabrics together.

[0050] In the present invention, it is particularly preferable that nonwoven fabric layer B be composed of polyolefin fibers chemically bonded with iminodiethanol groups, because this has a high metal removal efficiency. Regarding the metals that can be adsorbed, sulfonic acid groups mainly adsorb Na, Cu, and K, while iminodiethanol groups mainly adsorb Cr, Al, and Fe.

[0051] The polyolefin fibers constituting the nonwoven fabrics A and B are preferably long fibers. This is because long fiber nonwoven fabrics are less likely to generate fiber waste and have high filtering performance. In particular, a high mass per area (basis weight) of 10 to 100 g / m is preferred. 2 The melt-blown long fiber nonwoven fabric is preferred.

[0052] The average single fiber diameter of the polyolefin fibers constituting the nonwoven fabrics A and B is preferably 0.2 to 10 μm. Within this range, the filtering performance is high. In addition, the surface area (specific surface area) can be increased, which also increases the substrate surface area for the graft polymerization reaction, thereby increasing the graft rate.

[0053] The polyolefin fiber is preferably one selected from polypropylene, a copolymer of propylene and ethylene, polyethylene, or a copolymer of ethylene and another α-olefin having 4 or more carbon atoms, and high-density polyethylene is particularly preferred. These polymers are inert, stable to chemical solutions, and capable of graft polymerization.

[0054] The filter cartridge is preferably a filter cartridge including a hollow inner tube and a filtration base fabric, the filtration base fabric being a nonwoven fabric in which metal adsorption groups are chemically bonded to polyolefin fibers, and the filtration base fabric is wound around the hollow inner tube to form a laminated structure.

[0055] The filter of the present invention is a filter incorporating the filter cartridge. The filter cartridge has a filtration base fabric wound around an inner tube and housed in a container. When the filter cartridge is incorporated into the filter container, the filter is housed in the container and then incorporated into the filter. In the case of a cartridge-type filter, the filter function can be restored by replacing only the filter cartridge, but the present invention also includes, for example, capsule-type filters in which the entire filter container is replaced. In the case of a capsule-type filter, the part corresponding to the filter cartridge is the filtration section.

[0056] Next, we will explain how to chemically bond various functional groups to polyolefin fibers. The polyolefin fibers are irradiated with radiation such as electron beams or gamma rays and then contacted with an emulsion containing a reactive monomer such as GMA, or the polyolefin fibers are contacted with an emulsion containing a reactive monomer and then irradiated with radiation such as electron beams or gamma rays to graft polymerize the reactive monomer onto the polyolefin fibers. When irradiating with electron beams, an irradiation dose of 1 to 200 kGy, preferably 5 to 100 kGy, and more preferably 10 to 50 kGy, is generally achieved. The irradiation is preferably carried out under a nitrogen atmosphere. Commercially available electron beam irradiation devices can be used, such as area beam electron beam irradiation devices such as the EC250 / 15 / 180L (manufactured by Iwasaki Electric Co., Ltd.), EC300 / 165 / 800 (manufactured by Iwasaki Electric Co., Ltd.), and EPS300 (manufactured by NHV Corporation).

[0057] Specific examples of the graft polymerization method include liquid-phase graft polymerization, in which a nonwoven fabric is activated by irradiation with radiation such as gamma rays or electron beams, and then immersed in an emulsion containing water, a surfactant, and a reactive monomer to complete graft polymerization on the nonwoven fabric substrate. Next, functional groups, such as sulfonic acid groups, amino groups, N-methyl-D-glucamine groups, iminodiacetic acid groups, iminodiethanol groups, amidoxime groups, phosphate groups, carboxylic acid groups, and ethylenediaminetriacetic acid groups, i.e., ion exchange groups and / or chelating groups, are introduced into the graft chains formed on the substrate. The present invention is not limited to liquid-phase graft polymerization, and other methods may also be used, such as gas-phase graft polymerization, in which polymerization is carried out by contacting the substrate with monomer vapor, and impregnation-gas-phase graft polymerization, in which the substrate is immersed in a monomer solution and then removed from the monomer solution to carry out the reaction in the gas phase. Representative chemical formulas of functional groups are shown in (Chemical Formula 5) for a sulfonic acid group (SC group), in (Chemical Formula 6) for an iminodiethanol group (IDE group), in (Chemical Formula 7) for an iminodiacetic acid group (IDA group), and in (Chemical Formula 8) for an N-methyl-D-glucamine group (NMDG group).

[0058] [ka]

[0059] [ka]

[0060] [ka]

[0061] [ka]

[0062] However, R in (Chemical Formula 5) to (Chemical Formula 8) is polyethylene (PE) + GMA (Chemical Formula 9) or polypropylene (PP) + GMA (Chemical Formula 10).

[0063] [ka]

[0064] [ka]

[0065] However, n and m in the above (Chemical Formula 9) to (Chemical Formula 10) are integers of 1 or more.

[0066] <Particulate removal filter> In the method for producing a composition for forming a coating film for lithography of the present invention, it is preferable that the precursor of the composition for forming a coating film for lithography is passed through the filter cartridge and then passed through a fine particle removal filter. Although a known fine particle removal filter can be used, the fine particle removal filter material is preferably at least one selected from the group consisting of polyethylene and nylon.

[0067] The pore size of the filter for removing fine particles is usually 30 nm or less, for example, 1 nm to 30 nm, for example, 1 nm to 20 nm, or preferably 1 nm to 10 nm.

[0068] <Metal reduction method> The metal reduction method of the present application is a method for reducing metals by filtering the above-described coating film-forming composition precursor for lithography using a filter cartridge, The cartridge filter is made by laminating or winding a plurality of types of filtering fabrics around a hollow inner cylinder, The filtering base fabric is a nonwoven fabric in which metal adsorption groups are chemically bonded to polyolefin fibers, The filtering base fabric includes a nonwoven fabric layer A and a nonwoven fabric layer B, The nonwoven fabric layer A is composed of polyolefin fibers to which sulfonic acid groups are chemically bonded as metal adsorption groups, In this method for reducing metals in a coating film-forming composition precursor for lithography, the nonwoven fabric layer B is a filter cartridge composed of polyolefin fibers to which at least one metal adsorption group selected from the group consisting of an amino group, an N-methyl-D-glucamine group, an iminodiacetic acid group, an iminodiethanol group, an amidoxime group, a phosphate group, a carboxylic acid group, and an ethylenediaminetriacetic acid group is chemically bonded.

[0069] By undergoing this step, metal impurities derived from the raw materials or solvent contained in the precursor of the coating film-forming composition for lithography can be reduced, and defects in the lithography step can be reduced.

[0070] By the above metal reduction method, various metal impurities (such as Na, Cu, Cr, Al, Fe, etc.) can be reduced to, for example, 0.5 ppb or less, for example, 0.4 ppb or less, for example, 0.3 ppb or less, for example, 0.2 ppb or less, for example, 0.1 ppb or less. The metal impurities can be quantified, for example, by the method described in the Examples.

[0071] <Method of manufacturing a substrate having a resist pattern, and method of manufacturing a semiconductor device> The method for producing a substrate provided with a resist pattern and the method for producing a semiconductor device according to the present invention will be described below.

[0072] The substrate having a resist pattern according to the present invention can be produced by applying the above-mentioned composition for forming a coating film for lithography onto a semiconductor substrate and baking it.

[0073] Examples of semiconductor substrates onto which the composition for forming a coating film for lithography of the present invention can be applied include silicon wafers, germanium wafers, and wafers of compound semiconductors such as gallium arsenide, indium phosphide, gallium nitride, indium nitride, and aluminum nitride.

[0074] When a semiconductor substrate having an inorganic film formed on its surface is used, the inorganic film can be formed by, for example, ALD (atomic layer deposition), CVD (chemical vapor deposition), reactive sputtering, ion plating, vacuum deposition, or spin-coating (spin-on-glass: SOG). Examples of the inorganic film include polysilicon film, silicon oxide film, silicon nitride film, BPSG (Boro-Phospho Silicate Glass) film, titanium nitride film, titanium oxynitride film, tungsten nitride film, gallium nitride film, and gallium arsenide film.

[0075] The resist underlayer film-forming composition of the present invention is applied to such a semiconductor substrate using a suitable application method such as a spinner or coater. The composition is then baked using a heating means such as a hot plate to form a resist underlayer film. Baking conditions are typically selected from a baking temperature of 100°C to 400°C and a baking time of 0.3 to 60 minutes. Preferably, the baking temperature is 120°C to 350°C and the baking time is 0.5 to 30 minutes, more preferably, the baking temperature is 150°C to 300°C and the baking time is 0.8 to 10 minutes. The thickness of the resulting lithography coating film is, for example, 0.001 μm to 10 μm, preferably 0.002 μm to 1 μm, and more preferably 0.005 μm to 0.5 μm. Baking temperatures below the above ranges can result in insufficient crosslinking, potentially making it difficult for the resulting resist underlayer film to exhibit resistance to resist solvents or basic hydrogen peroxide aqueous solutions. On the other hand, if the baking temperature is higher than the above range, the resist underlayer film may be decomposed by heat.

[0076] Exposure is performed through a mask (reticle) to form a predetermined pattern. For example, i-line, KrF excimer laser, ArF excimer laser, EUV (extreme ultraviolet), or EB (electron beam) is used. An alkaline developer is used for development, with the development temperature selected from 5°C to 50°C and the development time selected from 10 to 300 seconds. Examples of alkaline developers include aqueous solutions of inorganic alkalis such as sodium hydroxide, potassium hydroxide, sodium carbonate, sodium silicate, sodium metasilicate, and aqueous ammonia; primary amines such as ethylamine and n-propylamine; secondary amines such as diethylamine and di-n-butylamine; tertiary amines such as triethylamine and methyldiethylamine; alcohol amines such as dimethylethanolamine and triethanolamine; quaternary ammonium salts such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, and choline; and cyclic amines such as pyrrole and piperidine. Furthermore, the aqueous solutions of these alkalis may be used by adding an appropriate amount of alcohols such as isopropyl alcohol or a nonionic surfactant. Among these, preferred developers are quaternary ammonium salts, more preferably tetramethylammonium hydroxide and choline. Furthermore, surfactants and the like can be added to these developers. Alternatively, development can be carried out with an organic solvent such as butyl acetate instead of an alkaline developer to develop the portions of the photoresist where the alkaline dissolution rate is not improved.

[0077] Next, the lithography coating film is dry-etched using the formed resist pattern as a mask. At this time, if the inorganic film is formed on the surface of the semiconductor substrate used, the surface of the inorganic film is exposed, and if the inorganic film is not formed on the surface of the semiconductor substrate used, the surface of the semiconductor substrate is exposed. Thereafter, the substrate is processed by dry etching to manufacture a semiconductor device. [Example]

[0078] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. <Synthesis Example 1> 800 g of monoallyl diglycidyl isocyanuric acid (manufactured by Shikoku Chemical Industry Co., Ltd.), 608 g of 3,3'-dithiodipropionic acid (manufactured by Sakai Chemical Industry Co., Ltd., trade name: DTDPA), and 53 g of triphenyl monoethyl phosphonium bromide, a quaternary phosphonium salt, as a catalyst were dissolved in 2191 g of propylene glycol monomethyl ether, heated, and stirred for 4 hours under a nitrogen atmosphere while maintaining the temperature at 120°C. The resulting reaction product was diluted with 3652 g of propylene glycol monomethyl ether to form a varnish solution, which was subjected to GPC analysis. The weight-average molecular weight, calculated as standard polystyrene, was approximately 7800. This reaction product contains a polymeric compound having a structural unit represented by the following formula (A-1):

[0079] [ka]

[0080] <Preparation Example 1> To 3575 g of a solution containing 715 g of the polymer compound obtained in Synthesis Example 1 above, 179 g of tetramethoxymethyl glycoluril [POWDERLINK (registered trademark) 1174, manufactured by Nippon Cytec Industries Co., Ltd.], 18 g of 4-hydroxybenzenesulfonic acid (PSA), 11 g of bisphenol S, 7 g of a surfactant (R-30N, manufactured by DIC Corporation), 86.3 kg of propylene glycol monomethyl ether, and 9.9 kg of propylene glycol monomethyl ether acetate were added to prepare a resist underlayer film-forming composition.

[0081] Example 1 90 kg of the resist underlayer film-forming composition obtained in Preparation Example 1 was mixed with one cartridge filter (10 inch) described in JP-A 2018-167223 (manufactured by Kurashiki Seni Kako Co., Ltd.) and a polyethylene filter Microgard TMFiltration was carried out for 24 hours at a filtration rate of 50 L / h using one UC Filter (model number: CWCF01MSTUC, manufactured by Nippon Entegris Co., Ltd.) and one Ultipleat P-Nylon nylon filter (model number: ABD1ANM3EH1, manufactured by Nippon Pall Co., Ltd.). The metal content of the filtered solution was measured using an ICP-MS (Agilent 8800, manufactured by Agilent Technologies, Inc.).

[0082] <Comparative Example 1> 90 kg of the resist underlayer film-forming composition obtained in Preparation Example 1 was filtered through a polyethylene filter Microgard TM Filtration was carried out for 24 hours at a filtration rate of 50 L / h using one UC Filter (model number: CWCF01MSTUC, manufactured by Nippon Entegris Co., Ltd.) and one Ultipleat P-Nylon nylon filter (model number: ABD1ANM3EH1, manufactured by Nippon Pall Co., Ltd.). The metal content of the filtered solution was measured using an ICP-MS (Agilent 8800, manufactured by Agilent Technologies, Inc.).

[0083] <Comparative Example 2> 1.8 kg of a strongly acidic ion exchange resin (XSC-1115-H, manufactured by Muromachi Chemical Co., Ltd.) was added to 90 kg of the resist underlayer film-forming composition obtained in Preparation Example 1, and the mixture was subjected to ion exchange in a batchwise manner for 4 hours, followed by filtration to remove the ion exchange resin. The resist underlayer film-forming composition after ion exchange was filtered using a polyethylene filter Microgard TM Filtration was carried out for 24 hours at a filtration rate of 50 L / h using one UC Filter (model number: CWCF01MSTUC, manufactured by Nippon Entegris Co., Ltd.) and one Ultipleat P-Nylon nylon filter (model number: ABD1ANM3EH1, manufactured by Nippon Pall Co., Ltd.). The metal content of the filtered solution was measured using an ICP-MS (Agilent 8800, manufactured by Agilent Technologies, Inc.).

[0084] <Metal concentration in organic solvent> The metal concentrations were measured after the treatment methods of Example 1, Comparative Example 1, and Comparative Example 2 were carried out, and the results are shown in Table 1.

[0085] [Table 1]

[0086] Table 1 shows that Example 1 can reduce metals more effectively than metal reduction by nylon filter filtration and metal reduction by ion exchange. [Industrial Applicability]

[0087] According to the present invention, it is possible to provide a composition for forming a coating film for lithography, in which the amount of metal impurities is particularly reduced.

Claims

1. A method for producing a coating film-forming composition for lithography, the method comprising the steps of: passing a precursor of a coating film-forming composition for lithography, the precursor comprising a polymer having a weight-average molecular weight of 800 or more and an organic solvent through both a metal-removing filter cartridge and a particulate-removing filter cartridge connected in series upstream or downstream of the metal-removing filter cartridge, at a filtration flow rate of 1 to 1000 L / hour for 3 to 144 hours, the method comprising the steps of: The metal removal filter cartridge comprises: A filter cartridge in which multiple types of filtration fabrics are laminated or wound around a hollow inner cylinder, The filtering base fabric is a nonwoven fabric in which a metal adsorption group is chemically bonded to a polyolefin fiber, The filtering base fabric includes a nonwoven fabric layer A and a nonwoven fabric layer B, The nonwoven fabric layer A is composed of polyolefin fibers to which sulfonic acid groups are chemically bonded as metal adsorption groups, The nonwoven fabric layer B is a filter cartridge characterized in that it is composed of polyolefin fibers having at least one metal adsorption group selected from the group consisting of an amino group, an N-methyl-D-glucamine group, an iminodiacetic acid group, an iminodiethanol group, an amidoxime group, a phosphoric acid group, a carboxylic acid group, and an ethylenediaminetriacetic acid group chemically bonded thereto.

2. The method according to claim 1, wherein the pore size of the particulate filter is 30 nm or less.

3. 3. The method according to claim 1, wherein the coating film-forming composition precursor for lithography is a resist underlayer film-forming composition, a protective film-forming composition for protecting a substrate from an etching solution during processing of a semiconductor substrate, an underlayer film-forming composition for a self-assembled film, an overlayer film-forming composition for a self-assembled film, or a resist overlayer film-forming composition.

4. 2. The method according to claim 1, wherein the particulate filter is made of at least one material selected from the group consisting of polyethylene and nylon.

5. The method according to claim 1 or 2, wherein the coating film-forming composition for lithography is a resist underlayer film-forming composition.

6. The method according to claim 5 , wherein the resist underlayer film forming composition further comprises a crosslinkable compound.

7. The method according to claim 5 or 6, wherein the resist underlayer film forming composition further comprises a crosslinking catalyst.

8. The method according to any one of claims 5 to 7, wherein the resist underlayer film forming composition further contains a surfactant.

9. A method for reducing a metal concentration in an organic solvent to 0.5 ppb or less, comprising a step of circulating a lithography coating film-forming composition precursor, the precursor comprising a polymer having a weight average molecular weight of 800 or more and an organic solvent, through both a metal-removing filter cartridge and a particulate-removing filter cartridge connected in series upstream or downstream of the metal-removing filter cartridge at a filtration flow rate of 1 to 1000 L / hour for 3 to 144 hours, The metal removal filter cartridge is formed by laminating a plurality of types of filtration fabrics or winding them around a hollow inner cylinder, and the filtration fabrics are nonwoven fabrics in which metal adsorption groups are chemically bonded to polyolefin fibers. The filtering base fabric includes a nonwoven fabric layer A and a nonwoven fabric layer B, The nonwoven fabric layer A is composed of polyolefin fibers to which sulfonic acid groups are chemically bonded as metal adsorption groups, The nonwoven fabric layer B is a filter cartridge composed of polyolefin fibers to which at least one metal-adsorbing group selected from an amino group, an N-methyl-D-glucamine group, an iminodiacetic acid group, an iminodiethanol group, an amidoxime group, a phosphoric acid group, a carboxylic acid group, and an ethylenediaminetriacetic acid group is chemically bonded as a metal-adsorbing group. A method for reducing metal in a coating film-forming composition precursor for lithography.

Citation Information

Patent Citations

  • Production method of lithographic resist composition

    JP2013092686A

  • Production method of composition for forming coating film for lithography and pattern formation method

    JP2016206500A

  • Filter cartridge and filter

    JP2018167223A

  • Photosensitive colored resin composition

    WO2016158863A1

  • Protective film formation composition including specified crosslinking agent, and pattern formation method in which same is used

    WO2017191767A1